Pre-service teachers’ beliefs about literature integration in English language teaching classrooms - (:unkn) unknown (My University, 2018)
In late 1990s, teacher cognition has emerged as an important field of inquiry as more and more research studieshave demonstrated that teachers’ cognitions influence their instructional decisions and activities (Borg, 2003). Inthe case of pre-service teachers, their beliefs are mainly influenced by their prior experience as learners while thesebeliefs also act as a filtering mechanism to process new information presented in teacher education programs(Borg, 2009). This study investigated changes in the beliefs about the use of literary texts in English languageteaching (ELT) of 65 pre-service teachers enrolled at the teacher education department of a state university inIstanbul, Turkey. The inclusion of literature in ELT classrooms has been viewed as a beneficial process as itcontributes to students’ linguistic development, appreciation of different cultures, personal involvement, andindividual growth (Carter & Long, 1991). To that extent, ELT teacher education programs in Turkey have beenoffering courses to equip pre-service teachers with the knowledge and skills on how to integrate literature intolanguage teaching. The present study explored prior experiences and beliefs of pre-service English as a ForeignLanguage (EFL) teachers about literature integration and compared them with those formed after the completionof a two-semester course on teaching English through literature. Data were collected through open-endedquestionnaires administered before and after the course and subjected to content analysis as suggested by Weber(1990). Results showed that pre-service teachers had positive beliefs about literature integration while the coursehad some limited impact on their prior beliefs.

Öğretmenlerin bilişlerinin öğretime dair kararlarını ve aktivitelerini etkilediği bir çok bilimsel çalışma tarafından gösterildiğinden, 1990’ların sonuna doğru öğretmen bilişi konusu önemli bir araştırma alanı olarak öne çıkmıştır (Borg, 2003). Söz konusu öğretmen adayları olduğunda, inanışlarının çoğunlukla kendi öğrenim deneyimlerine dayandığı, ve bu inanışların onlara öğretmen eğitimi veren programlarda sunulan yeni bilgileri işlerken ve anlamlandırırken, bir filtreleme görevi gördüğü bulunmuştur (Borg, 2009). Bu çalışma İstanbul Türkiye’de bulunan bir devlet üniversitesinde İngilizce öğretmenliği eğitimi alan 65 öğretmen adayının yabancı dil eğitiminde edebi metin kullanımı ile ilgili inanışlarındaki değişiklikleri incelemiştir. İngilizce öğretiminde edebi metinlere yer verilmesinin öğrencilerin dil gelişimlerine, farklı kültürlerin zenginliklerini fark etmelerine ve kişisel gelişimlerine yaptığı katkılara uzun zamandır dikkat çekilmektedir (Carter & Long, 1991). Bu bağlamda, Türkiye’deki İngilizce öğretmenliği programları da öğretmen adaylarının edebiyatı derslerine nasıl dahil edebilecekleri konusunda bilgi ve becerileri kazandırmak amaçlı dersler sunmaktadır. Söz konusu çalışma İngilizce öğretmen adaylarının iki sömestr süren Edebiyat Yoluyla İngilizce Öğretimi dersini almadan önce yabancı dil öğretiminde edebiyat kullanımıyla ilgili deneyimlerini ve inanışlarını irdelemiş, ve bunları ders sonrası inanışlarıyla karşılaştırmıştır. Çalışmanın verileri ders öncesi ve sonrasında uygulanan açık uçlu bir anket ile toplanmış ve toplanan verilere içerik analizi yapılmıştır (Weber, 1990). Çalışma, öğretmen adaylarının İngilizce öğretiminde edebiyat kullanılması ile ilgili olumlu inanışlara sahip olduğunu; bununla beraber, ilgili dersin öğretmen adaylarının inanışları üzerindeki etkisinin sınırlı olduğunu göstermiştir.
Öğretmen adaylarının İngilizce derslerine edebiyat dahil edilmesiyle ilgili inanışları
Keywords: Dil ve Dil Bilim